Issues and Actors in African Nonstate Conflicts: A New Data Set. Issue 5 (3rd September 2018) - von Uexkull, Nina; Pettersson, Therese
ABSTRACT: Armed nonstate conflict without the direct involvement of the state government is a common phenomenon. Violence between armed gangs, rebel groups, or communal militias is an important source of instability and has gained increasing scholarly attention. In this article, we introduce a data collection on conflict issues and key actor characteristics in armed nonstate conflicts that provides new opportunities for investigating the causes, dynamics, and consequences of this form of organized violence. The data builds on and extends the Uppsala Conflict Data Program Non-State Conflict data set by introducing additional information on what the actors in the conflict are fighting over, alongside actor characteristics. It covers Africa during the time period 1989–2011. The data set distinguishes between two main categories of issues, territory and authority, in addition to a residual category of other issues. Furthermore, we specify sub-issues within these categories, such as agricultural land/water as sub-issue for territory and religious issues for other issues. As actor characteristics, the data set notes whether warring parties received military support by external actors and whether religion and the mode of livelihood were salient in the mobilization of the armed group. The article presents coding processes, key features of the data set, and point to avenues for new research based on these data.